Interleukin‐4 receptor alpha signaling regulates monocyte homeostasis. Issue 10 (5th September 2022) - Haider, Patrick; Kral‐Pointner, Julia B.; Salzmann, Manuel; Moik, Florian; Bleichert, Sonja; Schrottmaier, Waltraud C.; Kaun, Christoph; Brekalo, Mira; Fischer, Michael B.; Speidl, Walter S.; Hengstenberg, Christian; Podesser, Bruno K.; et al.
Abstract: Interleukin‐4 (IL‐4) and its receptors (IL‐4R) promote the proliferation and polarization of macrophages. However, it is unknown if IL‐4R also influences monocyte homeostasis and if steady state IL‐4 levels are sufficient to affect monocytes. Employing full IL‐4 receptor alpha knockout mice (IL‐4Rα −/− ) and mice with a myeloid‐specific deletion of IL‐4Rα (IL‐4Rα f/f LysM cre ), we show that IL‐4 acts as a homeostatic factor regulating circulating monocyte numbers. In the absence of IL‐4Rα, murine monocytes in blood were reduced by 50% without altering monocytopoiesis in the bone marrow. This reduction was accompanied by a decrease in monocyte‐derived inflammatory cytokines in the plasma. RNA sequencing analysis and immunohistochemical staining of splenic monocytes revealed changes in mRNA and protein levels of anti‐apoptotic factors including BIRC6 in IL‐4Rα −/− knockout animals. Furthermore, assessment of monocyte lifespan in vivo measuring BrdU + cells revealed that the lifespan of circulating monocytes was reduced by 55% in IL‐4Rα −/− mice, whereas subcutaneously applied IL‐4 prolonged it by 75%. Treatment of human monocytes with IL‐4 reduced the amount of dying monocytes in vitro. Furthermore, IL‐4 stimulation reduced the phosphorylation of proteins involved in the apoptosis pathway, including the phosphorylation of the NFκBp65 protein. In a cohort of human patients, serum IL‐4 levels were significantly associated with monocyte counts. In a sterile peritonitis model, reduced monocyte counts resulted in an attenuated recruitment of monocytes upon inflammatory stimulation in IL‐4Rα f/f LysM cre mice without changes in overall migratory function. Thus, we identified a homeostatic role of IL‐4Rα in regulating the lifespan of monocytes in vivo.